ANALISIS KESEJAHTERAAN DAN KESEHATAN MENTAL PEKERJA TERHADAP KUALITAS KEHIDUPAN KERJA DI PT X - Adna Zelig Pasaribu (2023)
The quality of works life (QWL) refers to humanizing work life and emphasizing on the human factor. Based on preliminary studies that researchers have conducted, 6.25% of workers stated that they do not have a good quality of working life. If the quality of working life is not good, then this will indirectly have an impact on the company. This study aims to analyse quality of work life from well-being and mental health aspects of workers at PT X. This is a quantitative study with cross-sectional design. The sampling technique is quota sampling. The sample size determined used Lemeshow and obtained a minimum sample of 60 respondents, while the respondents who were successfully obtained were 92 respondents. The data source used in this study was primary data using questionnaires through Google Forms. After the data collected, data analysed using Chi-Square test. 52.2% of respondents experienced a low QWL. There is a relationship between aspects of health, good work, career development, lifestyle choices, financial well-being, mental health and QWL with p-value 0.000. It is expected that workers implement good lifestyle and attend training, while for companies it is expected to provide facilities in providing training and providing appropriate rewards or wages.